Bactericidal activity of 2-nitroimidazole against the active replicating stage of mycobacterium bovis BCG and mycobacterium tuberculosis with intracellular efficacy in THP-1 macrophages - Khan, Arshad; Sarkar, Sampa; Sarkar, Dhiman (International Journal of Antimicrobial Agents, 2008)
This study evaluated the antituberculous potential of 2-nitroimidazole under in vitro conditions. Minimal bactericidal concentrations of the compound against actively replicating Mycobacterium bovis BCG and Mycobacterium tuberculosis H37Ra were found to be 0.226 mu g/mL and 0.556 mu g/mL in enriched and minimal medium, respectively. Minimal inhibitory concentrations were > 100 times lower than reported antituberculous nitroimidazoles such as nitrofurantoin and furaltadone, indicating the greater potential of 2-nitroimidazole. No discernible effect of 2-nitroimidazole was seen on saprophytic Mycobacterium smegmatis and the representative bacterial strain Escherichia coli DH5 alpha, indicating the specificity of the molecule against tuberculous mycobacteria. The compound was also found to be effective against M. tuberculosis in the intracellular environment of the human monocytic cell line THP-1, with a reduction in viability of bacilli by 2.5 log after 144 h of incubation at a concentration of 0.113 mu g/mL. A five-fold higher concentration (0.565 mu g/mL) of 2-nitroimidazole sterilised the macrophages of intracellular pathogens within 192 h, without affecting the host. However, 2-nitroimidazole was unable to affect significantly the viability of dormant non-replicating bacilli of M. bovis BCG and M. tuberculosis in Wayne's in vitro model. Overall, the results indicate that 2-nitroimidazole is a potent antituberculous agent active against the organism's active replicating stage, with promising intracellular efficacy as well. (c) 2008 Elsevier B.V. and the International Society of Chemotherapy. All rights reserved.
Keywords: 2-nitroimidazole; antimycobacterial agents; nitroimidazoles; THP-1 macrophage; tuberculosis

Method to extract intact and pure RNA from mycobacteria - Akhtar, Shamim; Sarkar, Sampa; Mishra, Abhishek; Sarkar, Dhiman (Analytical Biochemistry, 2011)
We describe a high-yielding, simple, and aerosol-free protocol for the isolation of RNA from mycobacteria that does not require sophisticated instruments. The method yielded 50 mu g of RNA from 10(7) cells, 50 times more than a recently reported method. Our method can extract total RNA from aerobically grown bacteria and from in vitro hypoxia-induced dormant bacilli and mycobacteria residing within infected macrophages. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Dormant; Hypoxia; Mycobacteria; RNA isolation; Spheroplast; Trizol

Potential use of nitrate reductase as a biomarker for the identification of active and dormant inhibitors of mycobacterium tuberculosis in a THP1 infection model - Sarkar, Sampa; Sarkar, Dhiman (Journal of Biomolecular Screening, 2012)
The development of a macrophage-based, antitubercular high-throughput screening system could expedite discovery programs for identifying novel inhibitors. In this study, the kinetics of nitrate reduction (NR) by Mycobacterium tuberculosis during growth in Thp1 macrophages was found to be almost parallel to viable bacilli count. NR in the culture medium containing 50 mM of nitrate was found to be optimum on the fifth day after infection with M. tuberculosis. The signal-to-noise (S/N) ratio and Z-factor obtained from this macrophage-based assay were 5.4 and 0.965, respectively, which confirms the robustness of the assay protocol. The protocol was further validated by using standard antitubercular inhibitors such as rifampicin, isoniazid, streptomycin, ethambutol, and pyrazinamide, added at their IC90 value, on the day of infection. These inhibitors were not able to kill the bacilli when added to the culture on the fifth day after infection. Interestingly, pentachlorophenol and rifampicin killed the bacilli immediately after addition on the fifth day of infection. Altogether, this assay protocol using M. tuberculosis-infected Thp-1 macrophages provides a novel, cost-efficient, robust, and easy-to-perform screening platform for the identification of both active and hypoxic stage-specific inhibitors against tuberculosis.
Keywords: high-throughput screening; inhibitor; Mycobacterium tuberculosis; nitrate reductase; THP1

Self–assembled histidine acid phosphate nanocapsules as templates for multifunctional hollow platinum nanospheres in ionic liquid [BMIM][BF 4 ] for drug delivery - Soni, Sarvesh Kumar; Sarkar, Sampa; Sarkar, Dhiman; Coloe, Peter J.; Bhargava, Suresh Kumar; Bansal, Vipul (Proceedings of Chemeca, 2012)
During the past few decades, the design and fabrication of nano drug delivery vehicle has received considerable attention for incorporating multi-functionality, emphasizing transportation of anticancer drugs to tumour sites. Protein-based nanoparticles hold significant promise in the development of anticancer drug delivery systems since they have remarkable superiority in biocompatibility, biodegradability and natural metabolism in physiologic systems. Ionic liquids (ILs) are a class of solvents that are composed solely of ions (ILs – commonly referred as room temperature molten salts or room temperature ionic liquids). They have recently emerged as green solvents or green reaction media, because of their reported unique physico-chemical properties. We report for the first time the controlled self-assembly of Histidine Acid phosphatase (HAP) enzyme in the IL 1-butyl-3-methylimidazolium tetrafluoroborate [BMIM][BF 4 ], leading to the formation of HAP nanocapsules as template for synthesis of platinum nanospheres. These HAP nano-containers were loaded with an anticancer drug curcumin. We further demonstrated in vitro drug release and synergistic anticancer effect of these systems on three different cell lines viz. hepatocellular carcinoma (HepG2), breast cancer (MCF-7) and human acute monocytes (THP-1). The present work can extend our theoretical understanding on nano-bio interfacial molecular self assembly and will facilitate the motivated insights of inorganic/organic hybrid nano-materials/ nano-particles/ nano-objects and ionic liquids based multi functional drug delivery vehicles with synergistic combination chemotherapy for potential application in tumor targeting. INTRODUCTION During the past few decades, the design and fabrication of drug delivery vehicle has received considerable attention for incorporating multi-functionality emphasizing transportation of anticancer drugs to tumour sites. These nano drug delivery vehicles have many advantages including prolonged circulation time of the drugs (Duncan, 2003, Kiick, 2007) , improved drug targeting and solubility (Duncan, 2003, Kiick, 2007), higher payloads (Duncan, 2003) and controlled release of the therapeutics into the blood stream or the targeted tumour tissues (Uhrich et al. 1999, Duncan, 2003).

Phytase isozymes from aspergillus niger NCIM 563 under solid state fermentation: biochemical characterization and their correlation with submerged phytases - Bhavsar, Kavita P.; Buddhiwant, Priyanka; Soni, Sarvesh K.; Depan, Dilip; Sarkar, Sampa; Khire, Jayant Malhar (Process Biochemistry, 2013)
Aspergillus niger NCIM 563 produces dissimilar phytase isozymes under solid state and submerged fermentation conditions. Biochemical characterization and applications of phytase Phy III and Phy IV in SSF and their comparison with submerged fermentation Phy I and Phy III were studied. SSF phytases have a higher metabolic potential as compared to SmF. Phy I is tetramer and Phy II, III and IV are monomers. Phy I and IV have pH optima of 2.5 and Phy II and III have pH optima of 5.0 and 5.6, respectively. Phy I, III and IV exhibited very broad substrate specificity while Phy II was more specific for sodium phytate. SSF phytase is less thermostable as compared to SmF phytase. Phy land II show homology with other known phytases while Phy III and IV show no homology with SmF phytases and any other known phytases from the literature suggesting their unique nature. This is the first report about differences among phytase produced under SSF and SmF by A. niger and this study provides basis for explanation of the stability and catalytic differences observed for these enzymes. Exclusive biochemical characteristics and multilevel application of SSF native phytases determine their efficacy and is exceptional. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: A. niger; Isozymes; Phytase; Solid state fermentation; Submerged fermentation

Intrinsic therapeutic and biocatalytic roles of ionic liquid mediated self-assembled platinum-phytase nanospheres - Soni, Sarvesh K.; Sarkar, Sampa; Selvakannan, P. R.; Sarkar, Dhiman; Bhargava, Suresh Kumar (RSC Advances, 2015)
We herein report the inherent antitumor efficiency of self-assembled phytase enzyme nanospheres and enhance their efficiency by decorating with platinum nanoparticles and with the anticancer drug curcumin. Firstly, controlled self-assembly of phytase enzyme in an Ionic Liquid 1-butyl-3-methylimidazolium tetrafluoroborate [Bmim][BF4], led to the formation of therapeutically active phytase nanospheres. These nanospheres were further decorated with platinum nanoparticles by adding the platinum ions to these spheres and the nanoparticles formation was mediated by the specific interaction between the histidine residue (in active site of phytase enzymes) and the platinum ions and subsequent reduction of the ions into nanoparticles. The enzyme spheres act as a functional soft template for the as-formed platinum nanoparticles. These Platinum decorated hybrid biomacromolecular phytase nanospheres were loaded with the anticancer drug curcumin and all the different kinds of nanospheres were subjected to in vitro cytotoxicity for their anticancer effect on three different kinds of cancer cell lines i.e. MCF-7, Hep-G2 and THP-1 derived human macrophages. We observed a gradual increase in the anticancer effect caused by only phytase nanospheres (25%), platinum-phytase nanospheres (37%), phytase-curcumin (78%) and platinum-phytase-curcumin nanospheres (90%) that establishes this protein based system as a robust combinatorial drug delivery vehicle. The platinum-phytase spheres also proved their usability as a highly efficient green and reusable biocatalytic system for phytate degradation. The present work facilitates our understanding of ionic liquid based synthesis for multifunctional protein based drug delivery vehicles incorporating combinatorial chemotherapy for potential application as biopharmaceutical agents for tumor treatment and bio-catalysis.

Targeting dormant tuberculosis bacilli: results for molecules with a novel pyrimidone scaffold - Joshi, Rohit R.; Barchha, Avinash; Khedkar, Vijay M.; Pissurlenkar, Raghuvir R. S.; Sarkar, Sampa; Sarkar, Dhiman; Joshi, Rohini R.; Joshi, Ramesh A.; Shah, Anamik K.; Coutinho, Evans C. (Chemical Biology & Drug Design, 2015)
Our inability to completely control TB has been due in part to the presence of dormant mycobacteria. This also renders drug regimens ineffective and is the prime cause of the appearance of drug-resistant strains. In continuation of our efforts to develop novel antitubercular agents that especially target dormant mycobacteria, a set of 55 new compounds belonging to the pyrimidone class were designed on the basis of CoMFA and CoMSIA studies, and these were synthesized and subsequently tested against both the dormant and virulent BCG strain of M.tuberculosis. Some novel compounds have been identified which selectively inhibit the dormant tuberculosis bacilli with significantly low IC50 values. This study reports the second molecule after TMC-207, having the ability to inhibit tuberculosis bacilli exclusively in its dormant phase. The synthesis was accomplished by a modified multicomponent Biginelli reaction. A classification model was generated using the binary QSAR approach - recursive partitioning (RP) to identify structural characteristics related to the activity. Physicochemical, structural, topological, connectivity indices, and E-state key descriptors were used for generation of the decision tree. The decision tree could provide insights into structure-activity relationships that will guide the design of more potent inhibitors.
Keywords: Antitubercular activity; dormant tuberculosis bacilli; pyrimidones; recursive partitioning

Detection of a target protein (GroEl2) in Mycobacterium tuberculosis using a derivative of 1,2,4-triazolethiols - Sarkar, Sampa; Swami, Sagar; Soni, Sarvesh Kumar; Holien, Jessica K.; Khan, Arshad; Korwar, Arvind M.; Likhite, Anjali P.; Joshi, Ramesh A.; Joshi, Rohini R.; Sarkar, Dhiman (Molecular Diversity, 2022)
Herein, we identified a potent lead compound RRA2, within a series of 54 derivatives of 1,2,4-triazolethiols (exhibit good potency as an anti-mycobacterial agents) against intracellular Mycobacterium tuberculosis (Mtb). Compound RRA2 showed significant mycobactericidal activity against active stage Mycobacterium bovis BCG and Mtb with minimum inhibitory concentration (MIC) values of 2.3 and 2.0 mu g/mL, respectively. At MIC value, RRA2 compound yielded 0.82 log reduction of colony-forming unit (cfu) against non-replicating Mtb. Furthermore, RRA2 compound was selected for further target identification due to the presence of alkyne group, showing higher selectivity index (> 66.66 +/- 0.22, in non-replicating stage). Using ``click'' chemistry, we synthesized the biotin linker-RRA2 conjugate, purified with HPLC method and confirmed the conjugation of biotin linker-RRA2 complex by HR-MS analysis. Furthermore, we successfully pulled down and identified a specific target protein GroEl2, from Mtb whole-cell extract. Furthermore, computational molecular modeling indicated RRA2 could interact with GroEl2, which explains the structure-activity relationship observed in this study.
Keywords: 1; 2; 4-triazolethiols; GroEl2; Mycobactericidal activity; Mycobacterium bovis BCG; Mycobacterium tuberculosis